Emergency broadcasting strategies for distributed robotic groups under limited communication. Issue 1 (May 2021) - Kenzin, Maksim; Bychkov, Igor; Maksimkin, Nikolai
Abstract: Execution of large-scale search and survey operations by groups of autonomous mobile robots requires the ability to respond to unforeseen events of different nature in a quick and efficient manner. In order to achieve this requirement, the available information about recent changes should be spread among all active group members as soon as possible. Informing a non-stationary group of mobile robots distributed across different regions of the operational area is a nontrivial task for large groups with limited communication capabilities. The paper addresses the problem of agent-based information distribution throughout a network in a new original formulation. In essence, the problem is to define an effective order of transferring data between single robots in order to achieve the fastest way of sharing it among the whole group. A number of heuristic strategies are proposed for building initial solutions alongside with the local search scheme for their further optimization. The comparison between the suggested approaches is made regarding both the solution quality and the speed of algorithm operation. Some issues related to the test instances generation are also considered.